Connecting the Dots Between the Gut–IGF-1–Prostate Axis: A Role of IGF-1 in Prostate Carcinogenesis - Matsushita, Makoto; Fujita, Kazutoshi; Hatano, Koji; De Velasco, Marco A.; Uemura, Hirotsugu; Nonomura, Norio (Frontiers in Endocrinology, 2022)
Prostate cancer (PCa) is the most common malignancy in men worldwide, thus developing effective prevention strategies remain a critical challenge. Insulin-like growth factor 1 (IGF-1) is produced mainly in the liver by growth hormone signaling and is necessary for normal physical growth. However, several studies have shown an association between increased levels of circulating IGF-1 and the risk of developing solid malignancies, including PCa. Because the IGF-1 receptor is overexpressed in PCa, IGF-1 can accelerate PCa growth by activating phosphoinositide 3-kinase and mitogen-activated protein kinase, or increasing sex hormone sensitivity. Short-chain fatty acids (SCFAs) are beneficial gut microbial metabolites, mainly because of their anti-inflammatory effects. However, we have demonstrated that gut microbiota-derived SCFAs increase the production of IGF-1 in the liver and prostate. This promotes the progression of PCa by the activation of IGF-1 receptor downstream signaling. In addition, the relative abundance of SCFA-producing bacteria, such as Alistipes, are increased in gut microbiomes of patients with high-grade PCa. IGF-1 production is therefore affected by the gut microbiome, dietary habits, and genetic background, and may play a central role in prostate carcinogenesis. The pro-tumor effects of bacteria and diet-derived metabolites might be potentially countered through dietary regimens and supplements. The specific diets or supplements that are effective are unclear. Further research into the “Gut–IGF-1–Prostate Axis” may help discover optimal diets and nutritional supplements that could be implemented for prevention of PCa.